Selective Surface Acoustic Wave-Based Organophosphorus Sensor Employing a Host-Guest Self-Assembly Monolayer of β-Cyclodextrin Derivative - Pan, Yong (Sensors (Basel), 2015)
Self-assembly and molecular imprinting technologies are very attractive technologies for the development of artificial recognition systems and provide chemical recognition based on need and not happenstance. In this paper, we employed a β-cyclodextrin derivative surface acoustic wave (SAW) chemical sensor for detecting the chemical warfare agents (CWAs) sarin (O-Isoprophyl methylphosphonofluoridate, GB). Using sarin acid (isoprophyl hydrogen methylphosphonate) as an imprinting template, mono[6-deoxy-6-[(mercaptodecamethylene)thio]]-β-cyclodextrin was prepared by self-assembled method on one of the SAW oscillators. After templates’ removal, a sensitive and selective molecular imprinting (MIP) monolayer for GB was prepared. Electrochemical impedance spectroscopy and atomic force microscope (AFM) were used to characterize this film. Comparing the detection results to GB by MIP film and non-MIP film, the molecularly imprinting effect was also proved. The resulting SAW sensor could detect sarin as low as 0.10 mg/m(3) at room temperature and the frequency shift was about 300 Hz. The response frequency increased linearly with increasing sarin concentration in the range of 0.7 mg/m(3)~3.0 mg/m(3). When sarin was detected under different temperatures, the SAW sensor exhibited outstanding sensitivity and reliability.